Eduwisata Bahari Berbasis Pemberdayaan Masyarakat dalam Pengembangan Taman Laut Olele, Kab. Bone Bolango, Provinsi Gorontalo - Marzaman, Atika; Rasyid, Ayub Usman (Jurnal Master Pariwisata (JUMPA), 2020)
This study seeks to propose a plan for sustainable development in the management of the Olele Marine Park area as an educational-tourism area based on community empowerment. Qualitative research methods with data collection techniques through surveys, interviews and focus group discussions. The results of the study explain the potential for the development of marine tourism in Olele Marine Park, Bone Bolango Regency. Olele as one local sea park has a very large tourism potential if viewed from its diversity of marine life. As for the obstacles are the low quality of the management of the tourism sector management both in terms of infrastructure and human resource capacity. In addition there has been no synchronization between the roles of the government, the private sector and the citizens of Olele Village, so that the development of a sustainable tourism sector cannot yet be achieved. Olele Beach, in fact, does not provide large economic benefits to the residents of Olele Village. The competition of tourism service providers has made Olele Village residents unable to reap profits and advantages from tourism sector. Keywords: marine tourism, Olele marine park, community empowerment.